Psychological Connection to the Gay Community and Negative Self-Appraisals in Middle-Aged and Older Men Who Have Sex With Men: The Mediating Effects of Fitness Engagement. (4th May 2021) - Brennan-Ing, Mark; Haberlen, Sabina; Ware, Deanna; Egan, James E; Brown, Andre L; Meanley, Steven; Palella, Frank J; Bolan, Robert; Cook, Judith A; Okafor, Chukwuemeka N; Friedman, M Reuel; Plankey, Michael W
Abstract: Objectives: Connections to the gay community may elicit negative self-appraisals among men who have sex with men (MSM), which may be exacerbated for people with HIV (PWH). Fitness engagement may mediate self-appraisals by maintaining or improving appearance and health. We hypothesized that gay community connections would be positively related to negative self-appraisal and explored whether this association would be mediated by fitness engagement and moderated by HIV status. Method: Data were obtained from the Multicenter AIDS Cohort Healthy Aging study ( N = 1, 026; PWH n = 525; people without HIV [PWOH] n = 501). Structural equation modeling (SEM) examined associations between gay community connections, negative self-appraisal (body image dissatisfaction, self-perception of aging), and fitness engagement (physical activity, motivation to be fit). Multiple-group SEM tested the moderating effects of HIV serostatus. Results: The SEM fit the data well (root mean square error of approximation = 0.056; 90% CI: 0.046, 0.066). Connection to the gay community was inversely related to negative self-appraisals and positively related to fitness engagement. Fitness engagement mediated the association between community connections and negative self-appraisal and was inversely related to negative self-appraisals. Among PWH, the association between community connections and self-appraisal was weaker and the effect of fitness engagement on negative self-appraisal was stronger compared to PWOH. Discussion: Connection to the gay community may be a source of resilience for aging MSM by lessening negative self-appraisals and promoting strategies that address body image dissatisfaction and self-perceptions of aging. Interventions facilitating connections to the gay community may support healthy aging in this population.